A Phenomenology of institutionalizing change [electronic resource] by Jonathan S. Dela Peña. - Dela Peña, Jonathan S. (Animo Repository, 2016)
Driven by the leadership roles of a Schools Division Superintendent (SDS) and the mandate of educational laws, the needed educational reforms and change initiatives reached a new comprehensive framework in this study. This qualitative research employing the Most Significant Change Technique (MSCT) as a phenomenological approach chronicled the need to unravel the phenomenology of the changes that occur in the schools of the Division of Misamis Occidental and to draw implications for institutionalizing change. In this study, four change initiatives were taken into account: GO: LCL, SUBA, DART and I am HIPHOP. Anchoring on the Theory of Change, it introduced a research framework which highlighted how leadership can be a factor in initiating projects that will bring about change in the educational setting. To find out how changes that resulted in improved performance outcomes in the Division were institutionalized in the school systems, the following problems are stated: i) How were the following change initiatives in the Division of Misamis Occidental implemented? ii) What were the Most Significant Change (MSC) stories derived from each of these initiatives? and iii) How can these change initiatives be institutionalized? With its aim to examine the phenomena of change in schools through the MSC stories that present the impact of change initiatives, it utilized key informant interview to document recounts of lived experiences of participants in the change process and the Interpretive Phenomenological Analysis (IPA) on the perception and beliefs of teachers, school heads and supervisors who are key informants in the educational delivery. Significant Change (SC) stories were collected using the MSC Protocol, analyzed and filtered up through a Focus Group (FG) composed of education officials, teachers and students. The chosen stories were verified by visiting the schools using the Checklist for School Visit and Survey Questionnaire comprising of Program Evaluation Survey Questionnaire and Key Informant Interviews (K